Taquinidos de la reserva nacional de Rio Clarillo (DIPTERA : TACHINIDAE ) - González, Christian R. (Acta Entomológica Chilena, 2022)
Thirty eight genera and 53 species of Tachinid (Díptera: Tachinidae) parasitic flies are reported in this paper as common and frequent in the National Reserve of Ihe Río Clarillo located at the foot steps of the Andes in our Región Metropolitana of Santiago (33e51‘Lat. S-705 29‘Long O). The examples were collected with net and Malaise trap during the wholc year around from September 1987 to September 1990. The natural vegetation of the Reserve is briefly described. The Subfamily Goniinae are the best represented at the Reserve. The known hosts of these 53 species are larvae or nymphs of several families of Lepidoptera, of Coleóptera, and Hemiptera and may be other so far undetecled Orders of Insects. The preserved examples are deposited at the Insects Collection of the Instituto de Entomología, Santiago.